Effect Produced by a Cyclooctyne Derivative on Both Infarct Area and Left Ventricular Pressure via Calcium Channel Activation - Lauro, Figueroa-Valverde; Marcela, Rosas-Nexticapa; Maria, López-Ramos; Francisco, Díaz-Cedillo; Magdalena, Alvarez-Ramirez; Virginia, Mateu-Armad Maria; Montserrat, Melgarejo-Gutierrez (Drug Research, 2022)
Background There are reports which indicate that some cyclooctyne derivatives may exert changes in cardiovascular system; however, its molecular mechanism is not very clear.Objective The aim of this study was to evaluate the biological activity of four cyclooctyne derivatives (compounds 1 to 4) produced on infarct area and left ventricular pressure.Methods Biological activity produced by cyclooctyne derivatives on infarct area was determinate using an ischemia/reperfusion injury model. In addition, to characterize the molecular mechanism of this effect, the following strategies were carried out as follows; i) biological activity produced by cyclooctyne derivative (compound 4) on either perfusion pressure or left ventricular pressure was evaluated using an isolated rat heart; ii) theoretical interaction of cyclooctyne derivative with calcium channel (1t0j protein surface) using a docking model.Results The results showed that cyclooctyne derivative (compound 4) decrease infarct area of in a dose-dependent manner compared with compound 1 to 3. Besides, this cyclooctyne derivative increase both perfusion pressure and left ventricular pressure which was inhibited by nifedipine. Other theoretical data suggests that cyclooctyne derivative could interact with some aminoacid residues (Met83, Ile85, Ser86, Leu108, Glu114) involved in 1t0j protein surface.Conclusions All these data indicate that cyclooctyne derivative increase left ventricular pressure via calcium channel activation and this phenomenon could be translated as a decrease of infarct area.
Keywords: Cyclooctyne; derivative; infarct; ischemia; calcium channel.